2016
DOI: 10.1038/jid.2015.364
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Engineered Fibroblasts Expressing Codon-Optimized COL7A1 Restore Anchoring Fibrils in RDEB

Abstract: Cells therapies, engineered to secrete replacement proteins, are being developed to ameliorate otherwise debilitating diseases. Recessive dystrophic epidermolysis bullosa (RDEB) is caused by defects of type VII collagen, a protein essential for anchoring fibril formation at the dermal-epidermal junction. Whereas allogeneic fibroblasts injected directly into the dermis can mediate transient disease modulation, autologous gene-modified fibroblasts should evade immunological rejection and support sustained delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 43 publications
2
38
0
2
Order By: Relevance
“…As described in our study for RDEB cells (Fig. 4), and by others (Georgiadis et al, 2016;Goto et al, 2006;Jackow et al, 2016;Titeux et al, 2010), transduced fibroblasts produced COLVII that relocated at the DEJ. However, the long-term persistence of these cells in our TESs remains to be proven.…”
Section: Discussionsupporting
confidence: 86%
“…As described in our study for RDEB cells (Fig. 4), and by others (Georgiadis et al, 2016;Goto et al, 2006;Jackow et al, 2016;Titeux et al, 2010), transduced fibroblasts produced COLVII that relocated at the DEJ. However, the long-term persistence of these cells in our TESs remains to be proven.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we used cells that in a differentiated state produce physiological levels of correctly folded collagen VII (Kuhl et al, 2015). Introduction of collagen VII above physiological levels-for example, by using cells genetically modified to overexpress collagen VII or injecting pure recombinant collagen VII (Georgiadis et al, 2016;Hou et al, 2015)-may alter its stability by altering the ratio between collagen VII and its interaction partners or other proteins promoting collagen VII stability. Thus, the pharmacokinetic behavior of collagen VII likely has to be individually determined for each therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we and others have shown the capability of genetically corrected fibroblasts to improve skin cohesion in RDEB skin. Genetic modification was previously performed using a lentiviral vector (Chen et al, 2002;Georgiadis et al, 2016), a bacteriophage integrase (Ortiz-Urda et al, 2003b;Ortiz-Urda et al, 2002), and gamma retroviruses (Goto et al, 2006;Titeux et al, 2010). In these works, gene-corrected RDEB fibroblasts were delivered either by local injections (Ortiz-Urda et al, 2003;Woodley et al, 2003), intravenous injections (Woodley et al, 2007), or through transplanted skin equivalent (SE) using genetically corrected fibroblasts and keratinocytes (Goto et al, 2006;Titeux et al, 2010).…”
Section: Introductionmentioning
confidence: 99%